HISTOLOGICAL STUDY ON OPTIC TECTUM IN IRAQI WATER SNAKE TESSELATA TESSELATA - N.A. Al –BAKRI; Azhaar Raheem Hussien (مجلة بغداد للعلوم)
The   ceiling  of the  midbrain  has  a couple  of  optic  lobes  which  are  prominent  and  used  as  an  optic   center  that  reflex   what  it  receives  from   eye  retina   fibers.     The  histology of optic  tectum  has  been  studied  in  Iraqi  water  snake  natrix  tesselata  tesselata  .  It  was  found  that  the  number  of  optic  tectum  were  seven  main  strata  organized  from  the  outside  to  the  inside   as  follows :  the  stratum  zonula (SZ), the  stratum  opticum (SO),  the  stratum  fibrosum  et  griseum  superficialis  (SFGS),  the  stratum  griseum  central (SGC),  the  stratum  album  central (SAC),  the  stratum  griseum  periventricular (SGP),  and  the  stratum  album  periventricular (SAP).  the  three  last  strata  consider  deep  layers  on  the  optic  tectum